MAIN DIFFICULTIES EVIDENCED IN ORAL LANGUAGEIN CHILDREN AGED 3 TO 4 YEARS THROUGH THE ORALLANGUAGE TEST - Chaluisa Maiquez, Jessica Aracelly; Padilla Álvarez, Gisela Catalina (Tierra Infinita, 2023)
In the present study, the vocabulary level of students from 3 to 4 years of age from the GuillermoVinueza Fiscal School and the Jilgueritos Child Development Center located in the province ofNapo is compared. The method used is of the comparative type of cross- sectional design witha quantitative approach and descriptive scope, the standardized test Oral Language Assessment(ELO) was applied to a total population of 29 children and the level of oral language was compared in relation to auditory discrimination, phonological, syntactic and semantic aspects. The results show insignificant differences in the area of oral language development within all the aspects to be evaluated. It is concluded that language deficiency groups several factors suchas social, family, affective, economic, housing, tics, teacher training that directly affect thisarea.
Keywords: comparative; descriptive; standardized; language; deficiencies; environment; stimulation; auditory